2015
DOI: 10.1159/000437413
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Brains Are Made of These: A Dataset of the Numbers and Densities of Neuronal and Nonneuronal Cells in the Brain of Glires, Primates, Scandentia, Eulipotyphlans, Afrotherians and Artiodactyls, and Their Relationship with Body Mass

Abstract: Comparative studies amongst extant species are one of the pillars of evolutionary neurobiology. In the 20th century, most comparative studies remained restricted to analyses of brain structure volume and surface areas, besides estimates of neuronal density largely limited to the cerebral cortex. Over the last 10 years, we have amassed data on the numbers of neurons and other cells that compose the entirety of the brain (subdivided into cerebral cortex, cerebellum, and rest of brain) of 39 mammalian species spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
179
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 45 publications
12
179
1
1
Order By: Relevance
“…For example, the mass of the cerebral cortex as well as its neuronal density scale as functions of the number of cortical neurons that are shared across Afrotheria, Glires, Eulipotyphla, and Artiodactyla -but not primates. The latter are characterized by an evolutionarily derived scaling relationship that results in more cortical neurons building a given cortical volume compared to nonprimates [Herculano-Houzel et al, 2014a, 2015a. A similar pattern is found across primate and nonprimate "rest of brain" (RoB; the ensemble of brainstem, diencephalon, and striatum), with more neurons fitting in the primate RoB than in nonprimate structures of a similar mass.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…For example, the mass of the cerebral cortex as well as its neuronal density scale as functions of the number of cortical neurons that are shared across Afrotheria, Glires, Eulipotyphla, and Artiodactyla -but not primates. The latter are characterized by an evolutionarily derived scaling relationship that results in more cortical neurons building a given cortical volume compared to nonprimates [Herculano-Houzel et al, 2014a, 2015a. A similar pattern is found across primate and nonprimate "rest of brain" (RoB; the ensemble of brainstem, diencephalon, and striatum), with more neurons fitting in the primate RoB than in nonprimate structures of a similar mass.…”
Section: Introductionmentioning
confidence: 70%
“…All collection, dissection, tissue processing, and mathematical procedures were performed as in our previous studies to ensure that all data obtained could be compared directly to those already published for eutherian species [collected in Herculano-Houzel et al, 2015a]. Briefly, brains were either perfused or immersion-fixed with 4% paraformaldehyde, dissected according to similar criteria (as detailed below), and individual brain structures were subjected to isotropic fractionation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that sheep show some form of a structured map (61) and that ungulates in general possess similar neuronal scaling rules as rodents (62). The emergence of a structured map in larger rodents is, therefore, likely.…”
Section: 35 and 71) (C)mentioning
confidence: 99%
“…In all of our studies, cerebral cortex includes the hippocampus, all cortex lateral to the rhinal sulcus, and the underlying subcortical white matter; in a growing number of studies, gray and white matter have been examined separately, and that is mentioned explicitly in this review, where applicable. Cerebellum includes the cerebellar peduncles, subcortical white matter, and deep nuclei; rest of brain is the ensemble of hindbrain-midbrain-striatum-diencephalon (not including the cerebellum) [74]. The olfactory bulbs are counted separately, when available, which they often are not due to the difficulty of collecting them intact.…”
Section: Neurons Are Highly Variable In Density; Other Cells Not So mentioning
confidence: 99%